Music, special educational needs and inclusion - Rocha, Alberto (2022)
This work presents the results of a study about the importance of the use of Information and Communication Technologies (ICT) in the teaching and learning process of a female student with Trisomy 21 (T21), which reinforces musical concepts using Soundbeam. Guided by the principles of Inclusive Education and the assumption that ICT have an impact on the processes of Teaching and Learning, particularly those destined to students with Special Educational Needs (SEN) and specifically T21. A bibliographical review was carried out aiming at constituting the theoretical framework of the problem of the study, aiming at understanding and filling a difficulty of marking the rhythm, resorting to some strategies as a means to achieve goals and positive results in the process of teaching learning. The verified results of the application allowed to verify the high degree of motivation and interest revealed by the young person in the use of the TIC, as well as their capacity to use equipment of generalized use and not specifically adapted.